Pengembangan Perangkat Pembelajaran Berbasis Masalah Meggunakan Media Moodle Untuk Meningkatkan Keterampilan Berpikir Kritis Mahasiswa Pada Materi Gelombang - Lovy Herayanti; Syifaul Gummah; Bq Azmi Sukroyanti; Gunawan Gunawan; Muh. Makhrus (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2018)
E-learning is learning process through electronic media, especially internet. E-learning enables learners to learn or possess science no matter when and where. The goal of this study was to develop Moodle in problem-based learning in order to improve learnersÃ¢â¬â¢ critical thinking skills. . The study was a research and development (R&D) study conducted in four stages, i.e. preliminary study, developing design, testing Moodle as media for problem-based learning, and result dissemination. Subjects of this study were students of physic education program of Faculty of Mathematics and Science Education of IKIP Mataram who enrolled in Wave course. Data on critical thinking skills is collected through tests, where tests have been validated by experts. The results of the study indicate an increase in students' critical thinking skills. Moreover, students gave positive response towards the use of Moodle developed as media in problem-based learning.